Kajian Menaikkan Penggunaan Bahan Bakar Gas Untuk Transportasi Jalan Sekaligus Menekan Pencemaran Udara - Sitorus, Budi (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2011)
The use of fuel oil for transportation is the largest 56% of national consumption, and road transport which is the largest consuming 88%. In urban areas, transport causes 87% of air riollution that reduce air quality resulting from the use of fossil fuels. The use of gaseous fuels for transport has not grown significantly in part because of gas supply iifficulties. The main problem is haw to increase the use of gas fuel for road transport, especially in urban areas. Study goal is to formulate recommendations to raise the use of CNG for road transport. The benefit for reducing fossil fuel consumption without reducing public services. The method : s descriptive qualitative approach and comparison with developed countries. The study re;ults suggest that steps need to be taken from the development capacity of the source gas, 'ransmission and distribution, SPBG, slowfill and fast fill, socialization and supervision of nstallation of converter kits for public transportation, certification workshops, mechanics to nstall converter kit, pricing pro-society.Keywords: Increased, use of CNG road transport